Application of logical methods in expert analysis of automotive engine failures in operation - Khrulev, A. E.; Saraiev, O. V.; Saraieva, I.; Хрулєв, О. Е.; Сараєв, О. В.; Сараєва, І. Ю. (Харківський національний автомобільно-дорожній університет, 2023)
It is known that the causes of failures in automotive engines can be determined based on existing experience in studying various engine malfunctions. However, an analysis of known methods for determining the causes of car engine failures shows that their use in practice, including in diagnosing the technical condition of engines, requires a lot of work and highly qualified personnel that in many cases is practically ineffective. Logical-probabilistic methods are also known, including those based on fault tree analysis. However, it is not possible to use such models and methods in searching for the c auses of engine failure. Goal. The purpose of the study is to create a methodology for determining the causes of faults and failures in engine operation, which can be applied with help of a logical way and applicable not only by the specialists with expert level, but also the wide qualification. Methodology. The solution to this problem was found in several stages. Initially, by structuring the symptoms, a fault tree was constructed that logically describes the cause-and-effect relationships between the failure event and the original damage that caused it. Data from expert studies of engine failures were used to construct the graph. This was done for each of the engine failure types selected for analysis. Next, a modified (inverted) fault tree was developed for a finite number of selected failure types. Results. Obtained logical graphs allow you to perform a simple logical analysis in the opposite direction from the generally accepted one, from the event of a system failure to the basic damage events that cause it. After obtaining logical graphs for each type of failure, a modified engine fault tree can be compiled, common to the considered types of failures. Originality. The proposed method was widely used previously in the study of reliability of various technical systems, however, this method for the first time has been proposed to determine the causes of engine failures. Practical value. As a result of using the proposed methodology in practice, it it became possible to determine the causes of failure in the engine with enough reliability for practice and minimal time expenditure.
Застосування логічних методів під час експертного аналізу відмов автомобільних двигунів в експлуатації
Keywords: internal combustion engine; fault; failure; logical method; fault tree analysis; двигун внутрішнього згоряння; несправність; відмова; логічний метод; аналіз дерева відмов; 620.192, 620.2, 621.432; 10.30977/VEIT.2023.24.0.6